TERGERUSNYA NILAI BUDAYA TABUA MA T’NEK MESE PADA MASYARAKAT DESA OELBONAK DAN PENILAIAN MORAL-ETIS - Desiderius Metan; Wiwik Ira Handayani (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2021)
Oelbonak village people inherited Tabua Ma T'nek Mese culture from their ancestors as a spirit that animates all aspects of their social life. The culture fostered a principle that they must live unitedly and work together. However, the influence of modernization has led to certain attitudes, actions or practices from certain parties who want to build an individualistic life. Or in other words, there are certain people or groups who no longer want to cooperate or share work because they think it is detrimental or burden them in the terms of material or financial perspective. As a result, people began to live trapped in a materialistic and individualistic lifestyle. This deviation cannot be justified if it is reflected from the moral source of the Catholic religion (The Bible) and the assessment of ethical theory as well because it does not provide benefits, otherwise it is detrimental to oneself and others. Humans who have the Tabua Ma T'nek Mese culture (unified and one heart) are humans who always prioritize harmony, unity and brotherhood. Moreover, it can lead people to achieve the virtues of life, both horizontal virtues, namely the virtues of living with other humans and vertical virtues, namely the true happiness created through intimate fellowship with the owner and the provider of human life, The Almighty God.